Reverence, resistance and politics of seeing the Indian national flag - Jha, Sadan (New York : Cambridge University Press, 2016)
"Charts a history of the national flag of India in colonial and post-colonial periods and looks at the politics that go into the making of various discourses and ways of looking at the Indian national flag"--
Rise of the flag -- Flag on the Hut: totem and a political symbol -- The Indian national flag as a site of daily plebiscite -- Shades of history: a case of saffron colour -- Visualizing an ideal political order -- A post colonial symbol -- Gendered symbol, communal politics -- Epilogue: the flag as a sacred political symbol.
Includes bibliographical references (pages 247-264) and index.
Keywords: Flags -- India -- History